All in It Together? The Effects of Recession on Population Health and Health Inequalities in England and Sweden, 1991–2010. (January 2015) - Copeland, Alison; Bambra, Clare; Nylén, Lotta; Kasim, Adetayo; Riva, Mylène; Curtis, Sarah; Burström, Bo
This article is the first to comparatively examine the effects of two recessions on population health and health inequalities in the two historically contrasting welfare states of England and Sweden. Data from 1991–2010 on self-reported general health, age, gender, and educational status were obtained from the Health Survey for England, the Swedish Survey of Living Conditions, and the European Union Survey of Income and Living Conditions, for individuals aged over 16. Generalized linear models were used to test the effects of recessions on self-reported health and educational inequalities in health. Overall, recessions had a significant positive effect on the health of women—but not men—in both England (4%) and Sweden (7%). In England, this improvement was only enjoyed by the most educated women, with the health of less educated women declining during recession. In contrast, in Sweden, the health of all women improved significantly during recession regardless of their educational status, although the most educated benefitted the most. Relative educational inequalities in self-reported health therefore increased during recessions in both countries by 14 percent (England) and 17 percent (Sweden) but for different reasons. This study suggests that Sweden's welfare state protects the health of all during recessions.